Projections of irrigation water demand in India: what do recent trends suggest? - Amarasinghe, Upali A.; McCornick, Peter G.; Shah, Tushaar (2009)
Projected increases in irrigation water demand required to feed India's population have been a significant component of the justification for the ambitious and highly contentious India's National River Linking Project (NRLP), which, in its ultimate form, seeks to transfer water from relatively water-rich basins to those basins where demand has already outstripped supply. This paper re-examines some of the key assumptions underlying the irrigation demand estimations of the NRLP project, and concludes that a number of key assumptions are not consistent with recent trends. Major changes from earlier projections include rapidly changing consumption patterns and the dominance of groundwater as the source of irrigation water choice where available. The major challenge facing the agricultural water sector in India today and over the long term therefore is how to increase the groundwater stock (supply enhancement) to arrest declining groundwater tables, and how to sustain water use by minimizing uncontrolled groundwater pumping (demand management). While large-scale water developments, including inter-basin transfers, are likely still necessary, the characteristics of agricultural water demand and realities of available supplies need to be carefully reconsidered.